RECRUITMENT AND COMPENSATION FOR TEACHER PERFORMANCE IN PRIVATE VOCATIONAL SCHOOLS IN PAMIJAHAN SUB-DISTRICT BOGOR ACCREDITED B - Rahmawati, Ima; Lestari, Fitri; Lestari, Hana (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The purpose of this study was to determine the effect of recruitment and compensation on teacher performance in Private Vocational High Schools (SMK) in Pamijahan sub-district bogor accredited B. This study used quantitative research. The collected data in the form of numbers are analyzed by multiple linear regression analysis. This study used a questionnaire that was non-test. The questionnaire is systematically prepared by the researcher by submitting a written statement, answered by the respondent and returned to the researcher (Sugiyono, 2018). The questionnaire in this study was a closed questionnaire. The questionnaire in this study contained a series of statements, including five alternative answers to both positive and negative statements answered by teachers. Based on the regression test, a significant value of 0.000 < 0.05 was obtained, it can be concluded that there is a positive and significant influence between recruitment, compensation on teacher performance.